Ancient Egyptian furniture. 4000-1300 B.C. - Killen, Geoffrey (Oxbow Books, 2017)
This revised second edition examines the common forms of furniture used in ancient Egypt, so much of which has been preserved by the dry Egyptian climate and has long been admired for the quality of its design and construction. The story begins with the earliest known pieces and ends with the spectacular discoveries from the 18th dynasty represented mainly by the magnificent furniture from the tomb of Tutankhamun. The insight which Dr Killen brings in the detailed explanations of the materials, techniques and designs of the master craftsmen of ancient Egypt, gives this book a special significa.